Quotas : Data Update and Simulations. (Policy Papers; Policy Paper ;, 2016)
The quota database has been updated by one year through 2014. Overall, the results of the update continue the broad trends observed in previous updates, but the shifts between the main country groups are generally smaller. Using the current quota formula, the calculated quota share of Emerging Market and Developing Countries (EMDCs) as a group increases by 0.6 percentage points relative to the 2015 update to 49.3 percent, which is about half the increase in the last update. The paper takes stock of recent discussions on the quota formula, including the outcome of the Quota Formula Review in 2013 and subsequent discussions in the context of the annual quota data updates. It also updates the illustrative simulations of possible reforms of the quota formula presented previously, using the latest data. These simulations have sought to capture possible reforms that would be broadly in line with the conclusions of the Quota Formula Review and Directors' guidance is sought on the relative merits of these reforms and the most productive areas for future work. Download Quota Data: Updated IMF Quota Formula Variables - September 2016.